Photoluminescence Enhancement by Band Alignment Engineering in MoS2/FePS3 van der Waals Heterostructures - Ramos, Maria; Marques-Moros, Francisco; Esteras, Dorye L; Mañas-Valero, Samuel; Henríquez-Guerra, Eudomar; Gadea, Marcos; Baldoví, José J; Canet-Ferrer, Josep; Coronado, Eugenio; Calvo, M Reyes (ACS applied materials & interfaces, 2022)
Single-layer semiconducting transition metal dichalcogenides (2H-TMDs) display robust excitonic photoluminescence emission, which can be improved by controlled changes to the environment and the chemical potential of the material. However, a drastic emission quench has been generally observed when TMDs are stacked in van der Waals heterostructures, which often favor the nonradiative recombination of photocarriers. Herein, we achieve an enhancement of the photoluminescence of single-layer MoS2 on top of van der Waals FePS3. The optimal energy band alignment of this heterostructure preserves light emission of MoS2 against nonradiative interlayer recombination processes and favors the charge transfer from MoS2, an n-type semiconductor, to FePS3, a p-type narrow-gap semiconductor. The strong depletion of carriers in the MoS2 layer is evidenced by a dramatic increase in the spectral weight of neutral excitons, which is strongly modulated by the thickness of the FePS3 underneath, leading to the increase of photoluminescence intensity. The present results demonstrate the potential for the rational design of van der Waals heterostructures with advanced optoelectronic properties.Single-layer semiconducting transition metal dichalcogenides (2H-TMDs) display robust excitonic photoluminescence emission, which can be improved by controlled changes to the environment and the chemical potential of the material. However, a drastic emission quench has been generally observed when TMDs are stacked in van der Waals heterostructures, which often favor the nonradiative recombination of photocarriers. Herein, we achieve an enhancement of the photoluminescence of single-layer MoS2 on top of van der Waals FePS3. The optimal energy band alignment of this heterostructure preserves light emission of MoS2 against nonradiative interlayer recombination processes and favors the charge transfer from MoS2, an n-type semiconductor, to FePS3, a p-type narrow-gap semiconductor. The strong depletion of carriers in the MoS2 layer is evidenced by a dramatic increase in the spectral weight of neutral excitons, which is strongly modulated by the thickness of the FePS3 underneath, leading to the increase of photoluminescence intensity. The present results demonstrate the potential for the rational design of van der Waals heterostructures with advanced optoelectronic properties.